Ekspansi Dan Imperialisme Barat Kenegeri Negeeri Islam Hingga Jatuhnya Khalifah Utsmani Turki (LPPM Institut Al-Ma'arif Way Kanan, 2020)
The development of Islam in the early days of the glory was very trace in the history of world civilization until the time came when the glory collapsed and many western nations expanded their territory and led a part of the countries that were originally ruled by Islam. In a not too long time the western nation began to conduct strategies and discussions very rapidly in various fields such as medicine, economics, government, politics, culture and so on. The climax when the weakening of the Islamic empire which is very strong and respected throughout the world is the work of the development of Islam, it becomes an opportunity for Western nations to further bring down Islam and dominate the countries ruled by Islam. On the other hand Islam suffered many setbacks both in the internal problems of the kingdom and also the rebels to take advantage personally. The fall of the Turkish Ottoman Empire was a sad event that all Muslims in the world, the kingdom that ruled for centuries, in a short time can be torn down by western nation